Integrated biocircuits: engineering functional multicellular circuits and devices. (14th February 2018) - Prox, Jordan; Smith, Tory; Holl, Chad; Chehade, Nick; Guo, Liang
Abstract: Objective . Implantable neurotechnologies have revolutionized neuromodulatory medicine for treating the dysfunction of diseased neural circuitry. However, challenges with biocompatibility and lack of full control over neural network communication and function limits the potential to create more stable and robust neuromodulation devices. Thus, we propose a platform technology of implantable and programmable cellular systems, namely Integrated Biocircuits, which use only cells as the functional components of the device. Approach . We envision the foundational principles for this concept begins with novel in vitro platforms used for the study and reconstruction of cellular circuitry. Additionally, recent advancements in organoid and 3D culture systems account for microenvironment factors of cytoarchitecture to construct multicellular circuits as they are normally formed in the brain. We explore the current state of the art of these platforms to provide knowledge of their advancements in circuit fabrication and identify the current biological principles that could be applied in designing integrated biocircuit devices. Main results . We have highlighted the exemplary methodologies and techniques of in vitro circuit fabrication and propose the integration of selected controllable parameters, which would be required in creating suitable biodevices. Significance . We provide our perspective and propose new insights into the future of neuromodulaion devices within the scope of living cellular systems that can be applied in designing more reliable and biocompatible stimulation-based neuroprosthetics.